2019
DOI: 10.1016/j.beth.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Defining Treatment Outcomes in Pediatric Obsessive-Compulsive Disorder Using a Self-Report Scale

Abstract: This study examined benchmarks of treatment response and clinical remission on the Obsessive Compulsive Inventory-Child Version (OCI-CV) for youth with obsessive-compulsive disorder (OCD). Participants were 91 youth who enrolled in a randomized controlled trial that examined the benefit of augmenting cognitive behavior therapy (CBT) with either d-cycloserine or placebo. Youth completed the OCI-CV at baseline, Week 4 (prior to initiating exposure therapy), and posttreatment. Receiver operator curve (ROC) analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Further, change scores on the OCI-CV and the CY-BOCS were significantly correlated in the moderate range. These findings suggest that OCI-CV captures change in overall OCD severity reasonably well, and may be used alongside the CY-BOCS to provide complementary information about improvement in specific symptom dimensions, which is in line with the findings and recommendations by McGuire et al [19] for assessing treatment response based on the OCI-CV.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Further, change scores on the OCI-CV and the CY-BOCS were significantly correlated in the moderate range. These findings suggest that OCI-CV captures change in overall OCD severity reasonably well, and may be used alongside the CY-BOCS to provide complementary information about improvement in specific symptom dimensions, which is in line with the findings and recommendations by McGuire et al [19] for assessing treatment response based on the OCI-CV.…”
Section: Discussionsupporting
confidence: 85%
“…The authors observed a similar six-factor structure as in the original study, but suggested that these factors might be grouped under a second-order factor. Recently, the OCI-CV has also been proposed as an alternative measure to evaluate treatment response and clinical remission [19].…”
Section: Introductionmentioning
confidence: 99%
“…There were no studies testing CGI on U.S. child populations, even though it is in use as a child mental health measure—it appeared in 8 studies in our exploratory scan—and has been used as a benchmark to test other measures developed for children (e.g. the Obsessive–Compulsive Inventory—Child Version, see McGuire et al, 2019 ). This gap in testing may be partly because CGI was originally developed for schizophrenia (Guy, 1976 ) and only later adopted as a general measure of functioning.…”
Section: Results For Individual Measuresmentioning
confidence: 99%
“…Questionnaire results were analyzed in terms of improvement in total score from pre- to postintervention, including mean change in points, effect size (ie, Cohen d ), and percent of users with clinically significant improvement, defined as 20% improvement [ 65 , 66 ]. Results are presented separately for participants scoring in healthy and abnormal ranges at baseline, as per conventional clinical cutoff values.…”
Section: Methodsmentioning
confidence: 99%